2020
DOI: 10.3389/fpsyg.2020.01742
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Year Prospective Study of Socio-Professional and Psychological Outcomes in Students From High-Risk Schools Experiencing Academic Difficulty

Abstract: Early academic difficulty reduces the probability of pursuing higher education and has consequences for a wide range of personal and socio-professional outcomes. However, the role of academic performance is often difficult to assess independently from schoolbased influences. This prospective investigation uses a nested high-risk paradigm to examine the role of personal, familial and school-based factors in the prediction of 10-year outcomes. A sample of 131 secondary school students were selected based on scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Low performance of high school students and repeating a year are the problems most affecting education in Spain [ 2 ]. Beyond the implications for young people’s own professional development [ 4 , 13 ], low academic performance has been found to be a variable related to the appearance of other risks [ 3 , 5 , 8 , 9 , 10 ] impeding adolescent adjustment, such as school burnout [ 7 ]. As school adjustment is an important variable in adolescence as well as in the long-term, in adulthood [ 4 ], the objective of this study was to inquire into some of the factors involved, and particularly, to analyze the repercussion of low academic performance on burnout symptoms in high school students and the role of emotional intelligence in this relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low performance of high school students and repeating a year are the problems most affecting education in Spain [ 2 ]. Beyond the implications for young people’s own professional development [ 4 , 13 ], low academic performance has been found to be a variable related to the appearance of other risks [ 3 , 5 , 8 , 9 , 10 ] impeding adolescent adjustment, such as school burnout [ 7 ]. As school adjustment is an important variable in adolescence as well as in the long-term, in adulthood [ 4 ], the objective of this study was to inquire into some of the factors involved, and particularly, to analyze the repercussion of low academic performance on burnout symptoms in high school students and the role of emotional intelligence in this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Its influence on participation and commitment of adolescents in the school has been demonstrated [ 4 , 11 , 12 ]. And in the long term, academic problems related to lower academic performance and repeating a year have been associated with less likelihood of a higher education and precarious employment [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests Academic stakeholders are susceptible to impacts involving health, sociology, and achievement [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 31 , 32 , 33 , 34 , 35 ]. The generalization of Health as being the overall physical, mental, and emotional condition with regards to academic activities relevant to the individual.…”
Section: Methodsmentioning
confidence: 99%
“…A growing body of evidence has focused on the impact of environmental factors that affect cognitive development in early childhood, a critical phase in which environmental stimuli have a significant impact on brain architecture and cognition (Black et al 2017 ; Morais et al 2021 ; Johnson et al 2016 ; McCoy et al 2018 ; Britto et al 2017 ). Academic difficulties during preschool can reflect long-term personal and social problems in adulthood (Camara-Costa et al 2015 ; Salamon 2020 ). Studies have shown that learning difficulties in the preschool phase, such as math and reading skills (Rabiner et al 2016 ), have consequences on cognitive performance from preschool to higher education (Camara-Costa et al 2015 ; Salamon 2020 ) and have a negative impact on an individual’s ability to achieve high levels of education (Smart et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Academic difficulties during preschool can reflect long-term personal and social problems in adulthood (Camara-Costa et al 2015 ; Salamon 2020 ). Studies have shown that learning difficulties in the preschool phase, such as math and reading skills (Rabiner et al 2016 ), have consequences on cognitive performance from preschool to higher education (Camara-Costa et al 2015 ; Salamon 2020 ) and have a negative impact on an individual’s ability to achieve high levels of education (Smart et al 2017 ). Learning (defined as the acquisition of new knowledge and skills) is a complex human process primarily developed in early childhood when behaviors, skills, and knowledge are intensively acquired (Jirout et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%